Consideration of Shoulder Injury Prevention and Rehabilitation Exercise for Overhead Sports Population - Young Jin Jo; Young Kyun Kim (Asian Society of Kinesiology, 2019)
The main purpose of this article is to suggest orthopaedic-basic knowledge on evidence-based injury prevention and rehabilitation exercise for overhead sports activity population such as throwing, tennis, resistance training. Overhead sports activity population have glenohumeral joint internal rotation deficit (GIRD), excessive external rotation, posterior shoulder tightness (PST), abnormal scapular position and dyskinesis. These physical characteristics may elicit common shoulder injury such as subacromial impingement syndrome, rotator cuff tendinopathy, consequently range of motion improvement exercise and rotator cuff strengthening are needed in order to prevent it. Especially, sleeper stretching and horizontal adduction stretching are sports-specific technique to improve for GIRD and PST, external rotator cuff strengthening in side-lying position is recommended to adjust a balance strong internal rotator compared with weak external rotator for rotator cuff exercise. Therefore, exercise specialist should examine shoulder joint strength and range of motion before practical application, these exercise maneuvers can be used extensively for shoulder injury prevention as well as rehabilitation exercise.